Квантовые характеристики высвобождения нейропередатчика в ГАМК-эргических синапсах культивируемых нейронов спинного мозга крыс - Шипшина, М.С.; Веселовский, Н.С.; Федулова, С.А. (Нейрофизиология, 2009)
С использованием методов фиксации потенциала в конфигурации «целая клетка» и стимуляции отдельной пресинаптической терминали были исследованы некоторые особенности высвобождения ГАМК в тормозных синапсах культивируемых нейронов спинного мозга крыс. З використанням методів фіксації потенціалу в конфігурації «ціла клітина» та стимуляції окремої пресинаптичної терміналі були досліджені деякі особливості вивільнення ГАМК у гальмівних синапсах культивованих нейронів спинного мозку щурів. Using the whole-cell patch-clamp technique and stimulation of a single presynaptic terminal, we studied peculiarities of GABA release in inhibitory synapses of cultured neurons of the rat spinal cord. Analyzing the amplitude distributions of evoked inhibitory postsynaptic currents, we estimated the main quantum parameters of transmitter release. It was demonstrated that the minimum transmitter release in GABA-ergic synapses of spinal neurons cultured 9 to 11 days is multiquantum (packets containing at least 2 or 3 quanta). The distribution of the number of released quanta sufficiently agreed with that theoretically calculated according to the Poisson law. It is hypothesized that the minimum simultaneous two (three-)-quantum release of GABA in synapses of spinal neurons can be related to synchronous involvement of two closely adjacent excited terminals, each of which possesses one active zone, or of one terminal with two active zones. Using the whole-cell patch-clamp technique and stimulation of a single presynaptic terminal, we studied peculiarities of GABA release in inhibitory synapses of cultured neurons of the rat spinal cord. Analyzing the amplitude distributions of evoked inhibitory postsynaptic currents, we estimated the main quantum parameters of transmitter release. It was demonstrated that the minimum transmitter release in GABA-ergic synapses of spinal neurons cultured 9 to 11 days is multiquantum (packets containing at least 2 or 3 quanta). The distribution of the number of released quanta sufficiently agreed with that theoretically calculated according to the Poisson law. It is hypothesized that the minimum simultaneous two (three-)-quantum release of GABA in synapses of spinal neurons can be related to synchronous involvement of two closely adjacent excited terminals, each of which possesses one active zone, or of one terminal with two active zones.